ANTIMICROBIAL RESISTANCE PATTERN OF ENTERIC FEVER (Journal of Medical & Health Sciences Review, 2025)
Introduction: Enteric fever caused by Salmonella Typhi and Paratyphi is a significant public health concern, especially in developing countries. The emergence of antimicrobial resistance complicates its management. Resistance to first-line antibiotics like ampicillin, chloramphenicol, and co-trimoxazole is increasing, leading to the use of third-generation cephalosporins and fluoroquinolones. Yet, there is also a growing resistance to these newer antibiotics. This study assesses antimicrobial resistance in Salmonella Typhi isolates from pediatric patients.Methodology: In this study, 200 pediatric patients with enteric fever were included. Blood cultures were collected to test Salmonella Typhi isolates for antibiotic susceptibility using the Kirby-Bauer method. The antibiotics tested included first-line drugs, third-generation cephalosporins, fluoroquinolones, and aminoglycosides. Resistance patterns were analyzed based on demographic variables like gender, age, and residence.Results: Among the 200 cases, 63.5% were male and 36.5% female, with a mean age of 7.54 ± 3.12 years. Most cases (51.0%) were in children aged 1-7 years, with 49.0% in the 8-14 years group. Rural areas had a higher prevalence (52.5%) than urban areas (47.5%). Antibiotic resistance was high across various drug classes: Ampicillin (99.0%), ciprofloxacin (97.5%), ceftriaxone (97.0%), ceftazidime (94.5%), chloramphenicol (94.0%), aztreonam (93.5%), moxifloxacin (85.5%), levofloxacin (86.0%). Co-trimoxazole had lower but significant resistance (46.0%).Conclusion: A study found an alarming increase in drug resistance among Salmonella Typhi, especially to third-generation cephalosporins and fluoroquinolones. This stresses the need for antimicrobial programs, careful antibiotic use, and new treatment approaches for enteric fever.